2009
DOI: 10.1126/science.1166859
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity–Induced Gadd45b Promotes Epigenetic DNA Demethylation and Adult Neurogenesis

Abstract: The mammalian brain exhibits diverse types of neural plasticity, including activity-dependent neurogenesis in the adult hippocampus. How transient activation of mature neurons leads to long-lasting modulation of adult neurogenesis is unknown. Here we identify Gadd45b as a neural activity–induced immediate early gene in mature hippocampal neurons. Mice with Gadd45b deletion exhibit specific deficits in neural activity–induced proliferation of neural progenitors and dendritic growth of newborn neurons in the adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
820
0
7

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 852 publications
(862 citation statements)
references
References 29 publications
27
820
0
7
Order By: Relevance
“…This review will focus primarily on changes in histone modifications. However, we also note that regulators of DNA methylation are required for the function of a variety of adult stem cells (Zhao et al, 2003;Ma et al, 2009;Trowbridge et al, 2009;Sen et al, 2010;Trowbridge and Orkin, 2010;Wu et al, 2010), and that they complex with chromatin modifiers to elicit changes in chromatin state (Jones et al, 1998;Nan et al, 1998;Fuks et al, 2003). In addition, chromatin remodeling factors are also important for stem and progenitor cell function (Lessard et al, 2007;Ho et al, 2009;Ho and Crabtree, 2010), suggesting that several epigenetic mechanisms could coordinately control adult stem cell gene expression programs during organismal aging.…”
Section: Epigenetic Regulation Of Aging Stem Cellsmentioning
confidence: 74%
“…This review will focus primarily on changes in histone modifications. However, we also note that regulators of DNA methylation are required for the function of a variety of adult stem cells (Zhao et al, 2003;Ma et al, 2009;Trowbridge et al, 2009;Sen et al, 2010;Trowbridge and Orkin, 2010;Wu et al, 2010), and that they complex with chromatin modifiers to elicit changes in chromatin state (Jones et al, 1998;Nan et al, 1998;Fuks et al, 2003). In addition, chromatin remodeling factors are also important for stem and progenitor cell function (Lessard et al, 2007;Ho et al, 2009;Ho and Crabtree, 2010), suggesting that several epigenetic mechanisms could coordinately control adult stem cell gene expression programs during organismal aging.…”
Section: Epigenetic Regulation Of Aging Stem Cellsmentioning
confidence: 74%
“…Recent work by Métivier et al (2008) and Kangaspeska et al (2008) reveals a methylating-demethylating cycle of periodicity in the range of 30-50 min in mitotic cells. Another study found demethylation can occur between 4 and 120 h in post-mitotic neurons (Ma et al, 2009). Demethylation in these studies is characterized by site specificity (ie, to an individual cytosine address) and is coordinated with proteins involved in the removal of methylated cytosine in the aforementioned two step enzymatic process of deamination/base-excision.…”
Section: Demethylases: Removing the Markmentioning
confidence: 97%
“…Additional neuronal studies manipulating DNMT enzymes with knockdowns and pharmacological inhibitors provide further support for active promoter demethylation with consequential downstream changes in gene expression (Nelson et al, 2008;Noh et al, 2005;Sharma et al, 2008). Currently, this accumulating evidence of active demethylation of CpG dinucleotides as a direct consequence of neuronal activity and cellular signaling in post-mitotic neurons (Chen et al, 2003;Martinowich et al, 2003;Miller and Sweatt, 2007;Ma et al, 2009) has yet to be reconciled with a specific enzymatic mechanism.…”
Section: Demethylases: Removing the Markmentioning
confidence: 99%
See 2 more Smart Citations